Merging make-to-stock/make-to-order decisions into sales and operations planning: A multi-objective approach - Pereira, Daniel Filipe; Oliveira, José Fernando; Carravilla, Maria Antónia (Omega (Oxford), 2022)
•With the expansion of the product portfolio, companies are implementing Make-to-Stock (MTS) and Make-to-Order (MTO) policies to remain competitive.•In these companies, Sales and Operations Planning (S&OP) should balance the cost and service level associated with the fulfillment of each segment.•A multi-objective mixed-integer programming model can be useful to characterize the problem and obtain different mid-term plans.•Managers should frame and summarize the different Pareto-optimal plans considering the priority on MTS or MTO segments and the management preferences to promote effective S&OP meetings. With the advent of mass customization and product proliferation, the appearance of hybrid Make-to-Stock(MTS)/Make-to-Order(MTO) policies arise as a strategy to cope with high product variety maintaining satisfactory lead times. In companies operating under this reality, Sales and Operations Planning (S&OP) practices must be adapted accordingly during the coordinated planning of procurement, production, logistics, and sales activities. This paper proposes a novel S&OP decision-making framework for a flow shop/batch company that produces standard products under an MTS strategy and customized products under an MTO strategy. First, a multi-objective mixed-integer programming model is formulated to characterize the problem. Then, a matrix containing the different strategies a firm in this context may adopt is proposed. This rationale provides a business-oriented approach towards the analysis of different plans and helps to frame the different Pareto-optimal solutions given the priority on MTS or MTO segments and the management positioning regarding cost minimization or service level orientation. The research is based on a real case faced by an electric cable manufacturer. The computational experiments demonstrate the applicability of the proposed methodology. Our approach brings a practical, supply chain-oriented, and mid-term perspective on the study of operations planning policies in MTS/MTO contexts.